The crimes of the French occupation against The Rahmaniene Brotherhood in the Aures region during the 19th century CE" The Revolution of 1879 as an example - boughedada, elamir (The Algerian Historical Journal, 2026)
The aim of this study is to shed light on the criminal policy pursued by the French occupation against Rahmaniene Brotherhood in the Aures region during the nineteenth century AD, to break their authority and obstruct all their activities, as they were like the fuel of revolutions in the region against the French occupation. The Aures Revolution of 1879 led by Muhammad bin Abd al-Rahman or “Sheikh Boubarma” as he called by the French authority, which was in this, time El- Moukadam of El-Tarika Rahamania, is the most important example for anyone wants to study the crimes of the French occupation against the Algerian people and the Algerian respond. the crimes committed by the French authority was the cause of the outbreak of this revolution and during the process of conforming the Revolution the French committed more crimes and did not stop at an end. After the failure of the revolution, the measures were very harsh.